The structure and evolution of Thorne-Zytkow objects - Podsiadlowski, P (1996)
Thorne-Zytkow objects (TZOs) are red supergiants with neutron cores. The energy source in TZOs with low-mass envelopes (less than or similar to 8 Mo) is accretion onto the neutron core, while for TZOs with massive envelopes (greater than or similar to 14 M.) it is nuclear burning via the exotic rp process. TZOs are expected to form as a result of unstable mass transfer in high-mass X-ray binaries, the direct collision of a neutron star with a massive companion after a supernova or the collision of a neutron star with a low-mass star in a globular cluster. We estimate a birth rate of massive TZOs in the Galaxy of similar to 2 10(-4) yr(-1). Thus, for a characteristic TZO Lifetime of 10(5)-10(6) yr there should be 20-200 TiOs in the Galaxy at present. These can be distinguished from ordinary red supergiants because of anomalously high surface abundances of Lithium and rp-process elements, produced in the TZO interior. The TZO phase ends when either the star has exhausted its rp-process seed elements or the envelope mass decreases below a critical mass (similar to 14 M.). Then nuclear burning becomes inefficient and a neutrino runaway ensues, leading to the dynamical accretion of matter near the core onto the neutron star and its spin up to spin frequencies of up to similar to 100 Hz. The fate of the massive envelope is not entirely clear. If a significant fraction can be accreted onto the core, the formation of a black hole becomes Likely. Part of the envelope may collapse into a massive disk which may ultimately become gravitationally unstable and lead to the formation of planets or even low-mass stars. We discuss the various possible outcomes and suggest a possible link between massive TZOs and soft X-ray transients.